Correlation between plasma glutamate and adiponectin in patients with type 2 diabetes - Hirofumi Nagao; Hitoshi Nishizawa; Shiro Fukuda; Yuya Fujishima; Shunbun Kita; Norikazu Maeda; Takeshi Bamba; Eiichiro Fukusaki; Iichiro Shimomura (Endocrine Journal)
Visceral fat accumulation is a major determinant of type 2 diabetes mellitus and cardiovascular diseases. Recent studies have reported that glutamate is the most elevated amino acid in the plasma amino acid profile in patients with obesity and/or visceral fat accumulation. Here, we show the relationship between plasma glutamate and the clinical features of patients with type 2 diabetes. The study subjects were 62 (28 men and 34 women) Japanese patients with type 2 diabetes. Blood profiles, including glutamate and adiponectin (APN) levels and estimated visceral fat area (eVFA), were measured. We also evaluated the plasma amino acid levels in mice with or without obesity by GC/MS analysis. In patients with type 2 diabetes, plasma glutamate was positively correlated with BMI, eVFA, and fasting insulin but negatively correlated with APN and duration of diabetes. Additionally, multiple regression analysis revealed that plasma glutamate was a significant determinant of APN. The plasma glutamate level was most significantly increased in obese mice compared to control mice, and it was negatively correlated with APN. These results suggest that the level of plasma glutamate could be a strong indicator of adipocyte dysfunction in patients with type 2 diabetes.